Analysis of octane isomer properties via topological descriptors of line graphs - Alraqad, Tariq; Alameri, Abdu; Alsharafi, Mohammed; Louati, Hanen; Aldwoah, Khaled A.; Saber, Hicham; Gutman, Ivan (Springer Nature, 2024)
Currently, graph-based molecular structure descriptors are frequently used in QSAR (Quantitative Structure-Activity Relationship) and QSPR (Quantitative Structure-Property Relationship) modeling of the properties of chemical compounds. Octane isomers have an important role in the testing of such relationships. In this study, we compute some well-known topological descriptors of the molecular graphs of isomeric octanes and their line graphs, both indices and coindices. Then we analyze the correlation coefficients between the physicochemical properties of the octane isomers and some well-known topological indices and their coindices of the molecular graphs and the line molecular graphs of the octane isomers, to find the particular topological descriptors that have the best predictive values.